Low-cost data loggers for use with the conductivity mass balance method to estimate baseflow at snowmelt-dominated headwater streams in northwestern Colorado - Lidell, Amber Leigh, author; Sanford, William E., advisor; McGrath, Daniel, committee member; Covino, Tim, committee member (Colorado State University. Libraries, 2021)
Groundwater contribution to streamflow (baseflow) in snowmelt-dominated headwater streams, particularly following the snowmelt peak, is crucial for sustaining late season flow necessary for maintaining instream functions and fluvial ecosystems. Quantification of baseflow following snowmelt helps managers to determine the potential impacts of climate variability or management activities on streamflow, among others. One method of estimating baseflow is the conductivity mass balance (CMB), which requires continuous measurement of stream discharge and specific conductance (SC). Most headwater streams lack this information, as commonly used data loggers to measure SC are costly, and headwater streams have extreme variations in accessibility, temperature, discharge, and sediment. The purpose of this study is to investigate a new means to log continuous SC data in snowmelt-dominated headwater streams where data collection options are limited by costs. The primary objectives include deploying, calibrating, and testing a new low-cost data logger to continuously measure SC, gauging ungauged streams to determine continuous discharge, and estimating baseflow. The low-cost Stream Temperature, Intermittency, and Conductivity (STIC) data loggers were developed by modifying Onset HOBO Pendant waterproof temperature and light data loggers. 17 of these loggers as well as three higher-cost SC loggers were deployed in 10 streams in the Medicine Bow-Routt National Forests in northwestern Colorado in 2017 and/or 2018. Nine headwater streams were gauged, and rating curves developed to determine continuous discharge. 15 STIC loggers were then calibrated to known SC standards, and of those, in-stream data from 11 were used with discharge data to estimate baseflow at seven sites. Regression outputs for these 11 are available in the supplementary files. The conductivity-discharge relationships of two streams did not meet the requirements of the CMB method. Baseflow was also estimated at two streams with data from the higher-cost SC loggers. During the 2018 post snowmelt-dominated period, the data from STIC and higher-cost loggers recorded data that were used to calculate a proportion of baseflow to total streamflow (baseflow index) within 0.7 percent of one another at North Fork of the Elk River. Data from two STIC loggers that were deployed at Roaring Fork of Slater Creek were used to estimate baseflow indexes within 0.2 percent of one another. The data recorded by STIC loggers worked well with discharge data to estimate baseflow at seven sites with the CMB method during the post snowmelt-dominated portion of each hydrograph, even after being subjected to extreme field conditions. Once calibration and data processing time were taken into account, seven STIC loggers can be used for approximately the same cost as one higher-cost SC logger. For the best STIC logger data acquisition, it is recommended to deploy two low-cost loggers at each site as was done for this study, in a location that is not likely to experience heavy deposition, extremely turbulent flows, or long-term frozen water (e.g., in a glide or near a pool-tail crest). It is also recommended to calibrate the STIC loggers prior to field deployment, as was not done in this study. The findings of this study encourage the possibility of collecting more continuous data at more snowmelt-dominated headwater streams due to the low cost of these STIC loggers. This in turn increases potential for more baseflow data to be acquired at these streams, to inform and support public land and water management decisions and add to the active area of research surrounding baseflow estimation at headwater streams.
Zip file contains data documents.
Keywords: conductivity; headwater; specific conductance; continuous; baseflow; mass balance